Development of vegan burgers: a study with consumers and market research (Research, Society and Development, 2020)
The objective was to develop three formulations of vegan burger based on legumes, with evaluation of proximate composition and microbiological and sensory quality, and to perform market research on similar products available in Brazilian commerce. Formulations F1 (textured soy protein), F2 (red beans) and F3 (chickpeas) were developed and their direct costs per kg calculated. Coliforms at 45 °C, coagulase positive Staphylococci, Bacillus cereus and Salmonella spp. were investigated. Acceptance tests were applied, evaluating appearance, texture, flavor and global acceptance, and purchase intention. In formulations with a higher Acceptability Index (AI), for global acceptance, proximate composition and estimation of α-linolenic acid, dietary fiber and sodium were performed. Market research was carried out on similar products available in Brazilian commerce in 2020. The formulations were within the current legal standards. F3 stood out in all attributes, equaling F1 in appearance and global acceptance. However, F2 showed lower averages of appearance, flavor and global acceptance, with AI > 70%. 76% of the tasters would certainly buy the F3, which had higher values of moisture and lipids, with 1.96 g% of α-linolenic acid. F1 and F3 are protein sources, and F3 has a high fiber content. Of the 11 trademarks of similar products found, 9 mistakenly use the term "hamburger", and its protein bases are mainly legumes. The cost (R$) was 14.71 (F1), 12.16 (F2) and 12.52 (F3). The sodium content (mg%) was 699 (F1) and 466 (F3). Burgers can meet market demand at a more affordable cost.